Using Unnatural Protein Fusions to Engineer a Coenzyme Self-Sufficiency System for D-Phenyllactic Acid Biosynthesis in Escherichia coli - Qin, Zhao; Wang, Dan; Luo, Ruoshi; Li, Tinglan; Xiong, Xiaochao; Chen, Peng (Frontiers in Bioengineering and Biotechnology, 2021)
The biosynthetic production of D-penyllactic acid (D-PLA) is often affected by insufficient supply and regeneration of cofactors, leading to high production cost, and difficulty in industrialization. In this study, a D-lactate dehydrogenase (D-LDH) and glycerol dehydrogenase (GlyDH) co-expression system was constructed to achieve coenzyme NADH self-sufficiency and sustainable production of D-PLA. Using glycerol and sodium phenylpyruvate (PPA) as co-substrate, the E. coli BL21 (DE3) harboring a plasmid to co-express LfD-LDH and BmGlyDH produced 3.95 g/L D-PLA with a yield of 0.78 g/g PPA, similar to previous studies. Then, flexible linkers were used to construct fusion proteins composing of D-LDH and GlyDH. Under the optimal conditions, 5.87 g/L D-PLA was produced by expressing LfD-LDH-l3-BmGlyDH with a yield of 0.97 g/g PPA, which was 59.3% increased compared to expression of LfD-LDH. In a scaled-up reaction, a productivity of 5.83 g/L/h was reached. In this study, improving the bio-catalytic efficiency by artificial redox self-equilibrium system with a bifunctional fusion protein could reduce the bio-production cost of D-PLA, making this bio-production of D-PLA a more promising industrial technology.